2005
DOI: 10.1016/j.bbrc.2005.03.060
|View full text |Cite
|
Sign up to set email alerts
|

Hypergravity induces expression of cyclooxygenase-2 in the heart vessels

Abstract: Cyclooxygenase-2 (COX-2), a rate-limiting enzyme for prostaglandin biosynthesis, is induced by various stimuli including mechanical stress and plays important roles in pathophysiological conditions. For example, gravitational stress has been shown to induce expression of COX-2 in bone tissues, which is essential for bone homeostasis. To investigate whether COX-2 is induced by gravitational loading in other tissues than bone, we exposed mice to hypergravity at 2G and 3G for 4 h. We demonstrate here that COX-2 i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
20
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 24 publications
2
20
0
Order By: Relevance
“…COX-2 is not constitutively expressed in cardiomyocytes but is rather induced by various stress factors, e.g., cytokines, mechanical stress factors, or phenomena, that occur during ischemiareperfusion (1,21,(31)(32)(33). COX-2 is basally expressed in the cardiomyocytes used in our experiments.…”
Section: Role Of Cox-2 In the Negative Inotropic Effect Of Postischemmentioning
confidence: 94%
See 2 more Smart Citations
“…COX-2 is not constitutively expressed in cardiomyocytes but is rather induced by various stress factors, e.g., cytokines, mechanical stress factors, or phenomena, that occur during ischemiareperfusion (1,21,(31)(32)(33). COX-2 is basally expressed in the cardiomyocytes used in our experiments.…”
Section: Role Of Cox-2 In the Negative Inotropic Effect Of Postischemmentioning
confidence: 94%
“…COX-2 is inducibly expressed in cells (1,33). We therefore performed Western blot analysis to investigate whether COX-2 is expressed in isolated cardiomyocytes laminated and stained with fura-2 AM.…”
Section: Cox-2 Expression In Isolated Adult Cardiomyocytesmentioning
confidence: 99%
See 1 more Smart Citation
“…Two principal isoforms of COX, COX-1 and COX-2, have been identified. COX-1 is constitutively expressed in various normal tissues and exerts a variety of physiological functions, whereas COX-2 is rapidly induced in response to a number of stimuli, including growth factors and cytokines (Smith et al, 2000;Gupta and Dubois, 2001;Ricci et al, 2003;Oshima et al, 2005). Since many cancer tissues, including colorectal cancer tissues, produce various growth factors and cytokines (Bates et al, 1990;Salomon et al, 1995;Yarden and Sliwkowski, 2001;Tamura et al, 2002;Li et al, 2004;Montano and Djamgoz, 2004), COX-2 derived from advanced colorectal cancer cells seems to be induced by various growth factors and cytokines within the tumors (Bates et al, 1990;Eberhart et al, 1994;Salomon et al, 1995;Gupta and Dubois, 2001;Yarden and Sliwkowski, 2001;Tamura et al, 2002;Ricci et al, 2003;Li et al, 2004;Montano and Djamgoz, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Since opportunities for conducting animal experiments under microgravity are limited, experiments under hypergravity are important using special centrifugation apparatus (see below). The results from such hypergravity experiments We have previously demonstrated that short-term exposure to hypergravity at 2G for 4 h [2G (4H)] induces expression of cyclooxygenase-2 (COX-2; gene symbol, Ptgs2) in the heart [7]. COX-2 is a rate-limiting enzyme for prostaglandin biosynthesis, which plays important roles in a variety of pathological responses including tumorigenesis and diabetes [5,6,8].…”
mentioning
confidence: 99%